2006
DOI: 10.1021/jf052154+
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Compounds of Mezcal, an Ethnic Alcoholic Beverage Obtained from Agave salmiana

Abstract: Commercial mezcals (white, white with worm, rested, rested with worm, and aged) produced from Agave salmiana were analyzed by solid-phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS). Thirty-seven compounds were identified, and nine of them were classified as major compounds of mezcal (MCM). Saturated alcohols, ethyl acetate, ethyl 2-hydroxypropanoate, and acetic acid form the MCM group. Minor compounds of mezcal group include other alcohols, aldehydes, ketones, large chain ethyl esters, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 19 publications
0
102
0
3
Order By: Relevance
“…The solid-phase microextraction (SPME) method has been widely used in flavor analysis of wine (Ryan et al, 2005;Rodrigues et al, 2008;De León-Rodríguez et al, 2006). Luo et al (2008) identified a total of 97 volatile and semivolatile compounds using SPME-GC-MS; among them, 39 were volatile.…”
Section: -2008 (Shaoxing Rice Wine) Defines That Shaoxing Rice Wmentioning
confidence: 99%
“…The solid-phase microextraction (SPME) method has been widely used in flavor analysis of wine (Ryan et al, 2005;Rodrigues et al, 2008;De León-Rodríguez et al, 2006). Luo et al (2008) identified a total of 97 volatile and semivolatile compounds using SPME-GC-MS; among them, 39 were volatile.…”
Section: -2008 (Shaoxing Rice Wine) Defines That Shaoxing Rice Wmentioning
confidence: 99%
“…It seems likely that some of the phenols are formed during the cooking and/or distillation steps of mezcal production. Furthermore, naphthalene has been detected in mezcal from A. salmiana, sotol, and bacanora (Table 1) (López & Guevara 2001;De León-Rodríguez et al 2006).…”
Section: Minor Compoundsmentioning
confidence: 99%
“…Mezcal from Oaxaca has reached national and international recognition in the last few years, but at the moment the studies on the chemical compositions of different varieties are few. Several studies on the composition of volatiles have been performed on tequila and mezcal from A. salmiana, while there is little information on mezcal from A. angustifolia and A. potatorum (López & Guevara 2001;De León-Rodríguez et al 2006;Lachenmeier et al 2006). In addition, in most of these studies the geographic location, processing conditions, and aging time are not known.…”
mentioning
confidence: 99%
“…HS-SPME technique has been successfully used to identify the volatiles of aniseed flavored spirits such as raki, anis, pastis and sambuca (Jurado et al, 2007;De León-Rodríguez et al, 2008;Plutowska et al, 2010). Amongst other extractions techniques of volatiles, SPME appears to be effective, cheap and rapid method used in spirits (Capobiango et al, 2015) as long as the right fiber is chosen (Plutowska and Wardencki, 2008).…”
Section: Introductionmentioning
confidence: 99%